Approach to patients with hypophosphataemia. Issue 2 (February 2020) - Florenzano, Pablo; Cipriani, Cristiana; Roszko, Kelly L; Fukumoto, Seiji; Collins, Michael T; Minisola, Salvatore; Pepe, Jessica
Summary: Phosphate metabolism is an evolving area of basic and clinical research. In the past 15 years, knowledge on disturbances of phosphate homoeostasis has expanded, as has the discovery of new targeted therapies. Hypophosphataemia might be the biochemical finding in several diseases, and its clinical evaluation should initially focus on the assessment of pathophysiological mechanisms leading to low serum phosphate concentrations. Clinical consequences of hypophosphataemia can involve multiple organ systems and vary depending on several factors, the most important being the underlying disorder. This Review focuses on the approach to patients with hypophosphataemia and how underlying pathophysiological mechanisms should be understood in the evaluation of differential diagnosis. We define an algorithm for the assessment of hypophosphataemia and review the most up-to-date literature on specific therapies. Continuous research in this area will result in a better understanding and management of patients with hypophosphataemia.